Mediation role of service innovation in the effects of knowledge creation on marketing performance of restaurants - Kankam-Kwarteng, Collins; Osei, Francis; Asante-Gyabaah, Gabriel; Ferkah, Kofi Ankamah (Technium Social Sciences Journal, 2022)
This work explores the effect of knowledge creation on service innovation and marketing performance among restaurants within the Kumasi Metropolis. A total of 200 restaurants were sampled for this work. The study adopted the use of questionnaire as the main data collection instrument to obtain the study responses. The information obtained from the structured questionnaire was analyzed using the multiple linear regression technique for analyzing mediation effects to arrive at the study results. The findings of the study indicate that there is a positive relationship between knowledge creation and service innovation. It was also found that service innovation has positive and significant effect on marketing performance. Furthermore, the study findings revealed that service innovation mediates the relationship between knowledge creation and marketing performance of restaurants. Based on the results, it was recommended that management invest in the creation of knowledge as this will drive innovativeness in the organization and subsequently lead to a higher marketing performance. The paper significantly discusses the body of knowledge concerning the effect of knowledge creation, service innovation and marketing performance in the restaurant context.